2018
DOI: 10.3390/s18072060
|View full text |Cite
|
Sign up to set email alerts
|

Methods for the Real-World Evaluation of Fall Detection Technology: A Scoping Review

Abstract: Falls in older adults present a major growing healthcare challenge and reliable detection of falls is crucial to minimise their consequences. The majority of development and testing has used laboratory simulations. As simulations do not cover the wide range of real-world scenarios performance is poor when retested using real-world data. There has been a move from the use of simulated falls towards the use of real-world data. This review aims to assess the current methods for real-world evaluation of fall detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 50 publications
2
35
0
Order By: Relevance
“…Gait speed has been termed the sixth vital sign and has been reported to correlate with mortality [14,17]. Stride-to-stride variability of stride time, stride length, as well as swing time are examples of valid indicators for falls risk [18][19][20]. Recent studies showed that the gait characteristics in controlled lab settings and daily life settings are different [21,22].…”
Section: Gait Analysis With Imusmentioning
confidence: 99%
“…Gait speed has been termed the sixth vital sign and has been reported to correlate with mortality [14,17]. Stride-to-stride variability of stride time, stride length, as well as swing time are examples of valid indicators for falls risk [18][19][20]. Recent studies showed that the gait characteristics in controlled lab settings and daily life settings are different [21,22].…”
Section: Gait Analysis With Imusmentioning
confidence: 99%
“…In any case, this issue is just another example of the existence of a global problem associated with the research on fall detection systems: the lack of commonly accepted methodology to evaluate and benchmark the new proposals on FDSs existing in the literature. This lack of consensus, which has been highlighted and discussed by different authors [70][71][72][73], does not only affect the employed datasets, but also other important operational aspects of the evaluation policy (performance metrics, availability of the code of the proposed algorithms, etc.). Thus, the problem of the proper selection (number and typology of movements, participants, etc.)…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Two case studies were used to demonstrate the usefulness of this open source software. Broadley et al [34] presented a systematic review to assess existing methods of evaluating fall detection systems, identify their limitations, and propose improved evaluation methods in the literature. The search results of articles that met the inclusion criteria identified few issues, such as use of small population datasets and inconsistency for performance quantification for these systems.…”
Section: Summary Of Special Issue Papersmentioning
confidence: 99%